A novel preservative‐free seasonal influenza vaccine safety and immune response study in the frame of preclinical research. Issue 7 (28th March 2017) - Sarsenbayeva, Gulbanu; Volgin, Yevgeniy; Kassenov, Markhabat; Issagulov, Timur; Bogdanov, Nikolay; Nurpeisova, Ainur; Sagymbay, Altynay; Abitay, Ruslan; Stukova, Marina; Sansyzbay, Abylay; Khairullin, Berik
Abstract : The paper describes the results of preclinical testing of the preparation "Vaccine allantoic split‐virus inactivated against seasonal influenza." Acute toxicity and local irritating effect, anaphylactic reactions to different antigens (vaccine and ovalbumin), delayed‐type hypersensitivity to ram erythrocytes, humoral immune response in hemaggtination reaction, immunogenic activity was studied in laboratory animals of various species (mice, rats, guinea pigs). Comparative analysis of the results from testing immunogenic activity of the preparation under study and the commercial influenza vaccines was performed. The preclinical testing has demonstrated safety and immune response of the seasonal split influenza vaccine, so it may be recommended for clinical study on limited contingent of volunteers.